Pengaruh Profitabilitas pada Kebijakan Dividen dengan Investment Opportunity Set sebagai Variabel Pemediasi - Meidyna, Ida Ayu Nabila; Mertha, Made (E-Jurnal Akuntansi; Vol 30 No 1 (2020)DO - 10.24843/EJA.2020.v30.i01.p16, 2020)
The amount of dividends distributed to shareholders depends on the company's dividend policy. This study aims to obtain empirical evidence about the effect of profitability on dividend policy with an investment opportunity set as a mediating variable. This research was conducted at companies classified as LQ45 index on the Indonesia Stock Exchange. The sampling method used was purposive sampling to obtain 87 observations. Data analysis technique used is path analysis. Based on research results, it is known that profitability has a positive and significant effect on investment opportunity set. Profitability has a positive and significant effect on dividend policy. Investment opportunity set has a negative and significant effect on dividend policy. Investment opportunity set is able to mediate the effect of profitability on dividend policy. Keywords: Profitability; Investment Opportunity Set, Dividend Policy